Restauratio und memoria. Strategien des Wiederaufbaus in Annaberg nach dem großen Stadtbrand von 1604 - Silvestri, Marco (Im-materiell. Kulturerbe-Studien für Eva-Maria Seng zum 60. Geburtstag)

Income Shifting and Management Incentives - Ortmann, Regina; Schindler, Dirk

Wem gehört das Meer? Globale Ressourcen und die dritte UN-Seerechtskonferenz (1968–1994) - Sackel, Johanna

Sarah Ihden, Katharina Dreessen u. Robert Langhanke (Hgg.): Studien zur mittelniederdeutschen und frühneuhochdeutschen Sprache und Literatur, Hildesheim, Zürich u. New York: Olms 2021. - Wallmeier, Nadine (PBB)

Digitization in Catalysis Research: Towards a Holistic Description of a Ni/Al2O3Reference Catalyst for CO2Methanation - Weber, Sebastian; Zimmermann, Ronny T.; Bremer, Jens; Abel, Ken L.; Poppitz, David; Prinz, Nils; Ilsemann, Jan; Strübbe, Sven; Yang, Qingxin; Pashminehazar, Reihaneh; Monaco, Federico; Cloetens, Peter; et al. (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Low-code experimentation on software products - Gottschalk, Sebastian; Bhat, Rakshit; Weidmann, Nils; Kirchhoff, Jonas; Engels, Gregor (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)

 Zeitschrift für Romanische Sprachen und ihre Didaktik

 Zeitschrift für Romanische Sprachen und ihre Didaktik

Locking of microwave oscillators on the interharmonics of mode-locked laser signals - Bahmanian, Meysam; Kress, Christian; Scheytt, J. Christoph (Optics Express)
In this paper, the theory of phase-locking of a microwave oscillator on the interharmonics, i.e. non-integer harmonics, of the repetition rate of the optical pulse train of a mode-locked laser (MLL) is developed. A balanced optical microwave phase detector (BOMPD) is implemented using a balanced Mach-Zehnder modulator and is employed to discriminate the phase difference between the envelope of the optical pulses and the microwave oscillator. It is shown mathematically that the inherent nonlinear properties of BOMPD with respect to the microwave excitation amplitude can be used for interharmonic locking. The characteristic functions of the phase detector for interharmonic locking are derived analytically and are compared with the measurement results. An opto-electronic phase-locked loop (OEPLL) is demonstrated whose output frequency locks on interharmonics of the MLL repetition rate when an appropriate modulator bias and sufficient RF amplitude are applied. Thus, for the first time theory and experiment of reliable locking on interharmonics of the repetition rate of a MLL are presented.

High resolution off resonant spectroscopy as a probe of the oxidation state - Nowakowski, Michal; Kalinko, Aleksandr; Szlachetko, Jakub; Fanselow, Rafał; Bauer, Matthias (Journal of Analytical Atomic Spectrometry)
The direct conversion between HEROS-XES and XANES edge position (E0) without need of measuring absorption spectra.
Keywords: Spectroscopy; Analytical Chemistry

Asymptotic stability of spatial homogeneity in a haptotaxis model for oncolytic virotherapy. - Tao, Youshan; Winkler, Michael (Proceedings of the Royal Society of Edinburgh Section A: Mathematics)

Existence theory and qualitative analysis for a fully cross-diffusive predator-prey system - Tao, Youshan; Winkler, Michael (SIAM Journal on Mathematical Analysis)

Nonnegative solutions to a doubly degenerate nutrient taxis system - Li, Genglin; Winkler, Michael (Communications on Pure and Applied Analysis)

Who is that?! Does Changing the Robot as a Learning Companion Impact Preschoolers’Language Learning? - Tolksdorf, Nils Frederik; Hönemann, Dirk; Viertel, Franziska E.; Rohlfing, Katharina (Proceedings of the 2022 ACM/IEEE International Conference on Human-Robot Interaction)
In child-robot interaction research, many studies pursue the goal to support children's language development. While research in human-human interaction suggests that changing human partners during children's language learning can reduce their recall performance of the learning content, little is known whether a change in social robots as interaction partners influence children's learning in the same way. In this paper, we present findings from a word learning study, in which we changed the robotic partner for one group of children while the other group interacted with the same robot. Contrary to work with human social partners, we found that children did not retrieve words differently when interacting with different humanoid robots as their social interaction partners.

"Wir sind gekommen, doch wir sind gar nicht da" - Mythologische Formationen von Macht und Gewalt in Aischylos' "Die Schutzfllehenden" und Elfriede Jelineks "Die Schutzbefohlenen" - Böker, Ines (Mythos und Postmoderne. Mythostransformationen und mythische Frauen in zeitgenössischen Texten)

Armutssensibilität als religionspädagogische Herausforderung – Spannungsverhältnisse im fachdidaktischen Transfer der 'Option für die Armen' - Uppenkamp, Vera (Wissenstransfer. Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung)

Armutssensibilität im inklusiven Religionsunterricht - Uppenkamp, Vera (Handbuch der Religionen (73. Ergänzungslieferung))

Wirklichkeit(en) konstruieren: Die Mediendidaktik Deutsch als Säule oder Fundament? - Topalović, Elvira (Didaktik Deutsch)

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Quantum-state creation in nonlinear-waveguide arrays - Hamilton, Craig S.; Christ, Regina; Barkhofen, Sonja; Barnett, Stephen M.; Jex, Igor; Silberhorn, Christine (Physical Review A)